Optimizing the Utilization of Financial Literacy in Supporting Community Economic Development for Seafood Collectors and Micro-Businesses - Widia Astuty; Sri Rahayu; Azwansyah Habibie; Nabila Aliyya; Muhammad Husein Pasaribu (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service activity aims to enhance the financial management capabilities and financial literacy of residents in Bagan Deli Village, Medan Belawan District, as a strategic effort to strengthen the resilience of the local economy. The background of this program is rooted in the persistent challenges faced by the community, particularly the limited understanding of structured financial record-keeping, weak separation between personal and business finances, and low levels of financial literacy across multiple demographic groups. These conditions potentially hinder the growth of micro and small enterprises that form the backbone of the village economy. The primary targets of this activity include seafood collectors and micro-business actors who play a crucial role in local economic circulation but often lack access to practical financial education. The implementation of the program adopts a participatory and hands-on approach consisting of preliminary field observations, financial education sessions, and intensive mentoring. The educational component includes financial literacy socialization, practical training in simple bookkeeping systems, and guidance on utilizing digital platforms to support MSME promotion and market expansion. Throughout the mentoring phase, participants are encouraged to apply newly acquired knowledge directly to their daily financial practices, ensuring experiential learning and long-term retention. The results of the activity demonstrate a measurable improvement in participants’ awareness of systematic financial management, the importance of transparent record-keeping, and the productive use of digital technology in business operations. Overall, this community service initiative is expected to generate a sustainable impact by fostering disciplined financial behavior, strengthening entrepreneurial capacity, and contributing to the long-term economic welfare of the Bagan Deli community.